PENGEMBANGAN MEDIA BOOKLET PADA MATERI PERUBAHAN CUACA BERBASIS AUGMENTED REALITY MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS III SEKOLAH DASAR - Iswan, Muhammad; Alfi, Cindya; Fatih, Mohamad (STKIP Persada Khatulistiwa Sintang, 2024)
Integrated thematic learning is learning that is packaged in themes based on the integrated learning content. The aim of this research is to develop Augmented Reality-based Booklet media in order to further improve critical thinking skills of class III elementary school students. This research applied the research and development (R&D) method with ADDIE model which consists of 5 steps, namely analysis, design, development, implementation and evaluation. The instruments in this research are observation, interviews, tests and questionnaires. The data analysis technique used is quantitative descriptive analysis technique. The research results of this study can be seen from the average results of media experts for Augmented Reality-based Booklet media getting 4.95 which is stated